2004
DOI: 10.2136/sssaj2004.9240
|View full text |Cite
|
Sign up to set email alerts
|

Short‐Term Effects of Land Leveling on Soil Chemical Properties and Their Relationships with Microbial Biomass

Abstract: Spatial variability and distributions of soil chemical properties and the relationships between soil chemical and biological properties are not well characterized in agroecosystems that have been land leveled to facilitate more uniform delivery of irrigation water. The objectives of this study were to characterize the short‐term impacts of land leveling on the magnitudes, spatial variability, and spatial distributions of soil chemical properties and to evaluate the impact of land leveling on the relationships … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 23 publications
2
25
0
1
Order By: Relevance
“…The same behavior was found for the soil properties Tp, EC, P, Ca 2+ , Mg 2+ , Fe, Mn, Na, and MBC. However, under these circumstances, it may be affirmed, based on the determined dependence structures that the observations of each one of these properties depend on each other within the studied domain (Brye et al, 2004). Nielsen & Wendroth (2003) emphasize that the nugget effect may occur in the following situations: error in the laboratory process of soil sampling and laboratory analysis or due to the fact that the magnitude of spatial dependence is lower than the shortest distance between the sampled grid points (here 10 m), or possibly due to a combination of both situations.…”
Section: Resultsmentioning
confidence: 97%
“…The same behavior was found for the soil properties Tp, EC, P, Ca 2+ , Mg 2+ , Fe, Mn, Na, and MBC. However, under these circumstances, it may be affirmed, based on the determined dependence structures that the observations of each one of these properties depend on each other within the studied domain (Brye et al, 2004). Nielsen & Wendroth (2003) emphasize that the nugget effect may occur in the following situations: error in the laboratory process of soil sampling and laboratory analysis or due to the fact that the magnitude of spatial dependence is lower than the shortest distance between the sampled grid points (here 10 m), or possibly due to a combination of both situations.…”
Section: Resultsmentioning
confidence: 97%
“…The spatial variations of SOCD, STND, and STPD were large, with the coefficients of variation (CV) of >30% (Table 2). Although the CV is an index of the overall variation or heterogeneity of a given variable, the statistical analyses could not discern quantitative changes in spatial patterns (Brye et al 2004). Therefore, the spatial variations of SOCD, STND, and STPD were assessed using geostatistical analysis and kriging techniques.…”
Section: Spatial Variability Of Socd Stnd and Stpd In The Drained Amentioning
confidence: 99%
“…It was reported that eastern Arkansas silt-loam soils made alkaline from the use of high carbonate-containing irrigation water, and the availability of micronutrients generally decreases as soil pH increases (Norman et al, 2003). Land leveling frequently decreases bioavailability of Zn in these soils (Brye et al, 2004;Brye, 2006). Rice yields have been shown to increase on these soils when fertilized with inorganic N, P, and Zn (Miller, 1990;Miller et al, , 1991.…”
Section: Introductionmentioning
confidence: 99%